Rationale for the development of an Alzheimer's disease vaccine. Issue 3 (3rd March 2020) - Kwan, Ping; Konno, Haruki; Chan, Ka Yan; Baum, Larry
ABSTRACT: Vaccination traditionally has targeted infectious agents and thus has not heretofore been used to prevent neurodegenerative illness. However, amyloid β (Aβ) or tau, which can act like infectious proteins, or prions, might induce Alzheimer's disease (AD). Furthermore, evidence suggests that traditional infectious agents, including certain viruses and bacteria, may trigger AD. It is therefore worth exploring whether removing such targets could prevent AD. Although failing to treat AD patients who already display cognitive impairment, Aβ monoclonal antibodies are being tested in pre-symptomatic, at-risk individuals to prevent dementia. These antibodies might become the first AD therapeutics. However, their high cost will keep them out of the arms of the vast majority of patients, who increasingly live in developing countries. Because vaccines produce antibodies internally at much lower cost, vaccination might be the most promising approach to reducing the global burden of dementia.